Fast changes in seasonal forest communities due to soil moisture increase after damming - do Vale, Vagner Santiago (2013)
Local changes caused by dams can have drastic consequences for ecosystems, not only because they change the water regime but also the modification on lakeshore areas. Thus, this work aimed to determine the changes in soil moisture after damming, to understand the consequences of this modification on the arboreal community of dry forests, some of the most endangered systems on the planet. We studied these changes in soil moisture and the arboreal community in three dry forests in the Araguari River Basin, after two dams construction in 2005 and 2006, and the potential effects on these forests. For this, plots of 20m x10m were distributed close to the impoundment margin and perpendicular to the dam margin in two deciduous dry forests and one semi-deciduous dry forest located in Southeastern Brazil, totaling 3.6ha sampled. Besides, soil analysis were undertaken before and after impoundment at three different depths (0-10, 20-30 and 40-50cm). A tree (minimum DBH of 4.77cm) community inventory was made before (T0) and at two (T2) and four (T4) years after damming. Annual dynamic rates of all communities were calculated, and statistical tests were used to determine changes in soil moisture and tree communities. The analyses confirmed soil moisture increases in all forests, especially during the dry season and at sites closer to the reservoir; besides, an increase in basal area due to the fast growth of many trees was observed. The highest turnover occurred in the first two years after impoundment, mainly due to the higher tree mortality especially of those closer to the dam margin. All forests showed reductions in dynamic rates for subsequent years (T2-T4), indicating that these forests tended to stabilize after a strong initial impact. The modifications were more extensive in the deciduous forests, probably because the dry period resulted more rigorous in these forests when compared to semideciduous forest. The new shorelines created by damming increased soil moisture in the dry season, making plant growth easier. We concluded that several changes occurred in the T0-T2 period and at 0-30m to the impoundment, mainly for the deciduous forests, where this community turned into a “riparian-deciduous forest” with large basal area in these patches. However, unlike other transitory disturbances, damming is a permanent alteration and transforms the landscape to a different scenario, probably with major long-term consequences for the environment.